Effect of Problem-Based Learning on the Student Problem-Solving Skills - Nurvita Putri Utami; Fitria Wulandari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Science learning in elementary schools is expected to not only provide conceptual understanding but also foster students' ability to solve real-life problems through active learning. This study was conducted to measure the effect of Problem-Based Learning on the problem-solving ability of fifth-grade students of SDN Krembung 1 in learning science on the human respiratory system. The One Group Pretest-Posttest research design was used to test the instrument's validity and reliability, assess the normality and homogeneity of the pretest and posttest results, and determine the influence using the T Test. The instrument developed by the researcher was based on the problem-solving indicators developed by George Polya: (1) Understanding the problem, (2) Planning Problem Solving, (3) Implementing the problem-solving plan, and (4) Checking the Process and Results of problem solving. Problem-Based Learning is applied through five stages, namely: (1) Orientation to the problem, (2) organising students, (3) guiding the investigation, (4) developing and presenting results, and (5) analysing and evaluating the problem-solving process. The pretest was carried out first, followed by the application of the problem-based learning model, and then the posttest. The average pretest score was 79 (68–89), and the average posttest score was 90 (75–100). The results of the paired sample t-test analysis showed a significance value (2-tailed) of 0.000, which means there is a significant difference between the pretest and posttest results. These findings suggest that integrating Problem-Based Learning into classroom instruction not only enhances students’ problem-solving abilities but also aligns well with the goals of competency-based curricula such as the Merdeka Curriculum, which emphasize active learning and critical thinking. Thus, Problem-Based Learning is effective in improving students' problem-solving abilities.